2009
DOI: 10.1016/j.drugalcdep.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Access to drug and alcohol treatment among a cohort of street-involved youth

Abstract: Background-A number of options for treatment are available to young drug users, but little is known about the youth who actually attempt to access such services. Here we identify characteristics of a cohort of street-involved youth and highlight commonly encountered barriers. . Among those who experienced difficulty accessing services, the most commonly identified barrier was excessively long waiting lists. In a subgroup analysis comparing those who tried to access services but were unsuccessful to those who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…Currently, one of the most commonly employed points of contact with at-risk youth is the judicial system, and methamphetamine-using youth in particular appear more likely than their peers to have a history of incarceration and to have interactions with police [24] . However, imprisonment of high-risk youth carries costs that probably far exceed those of addiction treatment [35,36] , and may in fact be associated with greater transition to injection drug use [4,5] . In this light, greater efforts might be made to intervene early with street youth before they have negative interactions with police, and to develop alternative criminal justice interventions so that high-risk youth can be directed to addiction services rather than to prison.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, one of the most commonly employed points of contact with at-risk youth is the judicial system, and methamphetamine-using youth in particular appear more likely than their peers to have a history of incarceration and to have interactions with police [24] . However, imprisonment of high-risk youth carries costs that probably far exceed those of addiction treatment [35,36] , and may in fact be associated with greater transition to injection drug use [4,5] . In this light, greater efforts might be made to intervene early with street youth before they have negative interactions with police, and to develop alternative criminal justice interventions so that high-risk youth can be directed to addiction services rather than to prison.…”
Section: Discussionmentioning
confidence: 99%
“…Although free health insurance (e.g., Medicaid) and free healthcare is available, fulfilling eligibility requirements is often complicated by structural factors, such as an inability to show evidence of a fixed permanent address, birth certificate, or photo identification [105]. Some studies suggest that homeless youth are reluctant to access healthcare services, because of difficulty navigating the healthcare system, few clinic sites, lack of coordination among providers, specific hours for homeless youth, and long waitlists [9,106,107]. Additionally, many of the clinics that serve homeless individuals integrate child and adult services, which some homeless youth reports makes them uncomfortable [9].…”
Section: Access To Health Carementioning
confidence: 99%
“…These concerns might be warranted, as research with medical students has indicated that they hold more negative attitudes towards homeless people at the end of their medical training than when they began [110]. Another reason that many youth do not access healthcare is that they do not believe that they have a problem or need help [82,106]. This appears especially true of youth with substance use problems.…”
Section: Access To Health Carementioning
confidence: 99%
“…At-risk Canadian youth often face a barrage of difficulties in accessing care that meets the level of risk they present [36]. Indigenous peoples have some of the highest rates of substance use disorder in Canada, and face both barriers to accessing general treatment options, as well as programs that incorporate traditional healing practices [29,37].…”
Section: Marginalized Subgroupsmentioning
confidence: 99%